Self-Efficacy Toward Service, Civic Participation and the Business Student: Scale Development and Validation - Weber, Paula S. (Journal of business ethics, 2004)
This paper presents the development andvalidation of new measurement tools to exploreself-efficacy toward service and toward civicparticipation. We developed and administereda survey to 851 students in an AACSB-accreditedcollege of business at a comprehensive publicuniversity located in the Midwest. Traditionalscale development methodologies plusconfirmatory factor analysis and simultaneousfactor analysis in several populations wereused to analyze both a primary sample and aholdback sample. Results strongly support thevalidity and reliability of the surveyinstrument. Future use for the instrumentincludes verification of the effectiveness ofpedagogies designed to increase self-efficacytoward service and motivation for civicparticipation in business students.